2020
DOI: 10.1016/j.bej.2020.107533
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic characterization within a spinner flask and a rotary wall vessel for stem cell culture

Abstract: • CFD simulations of a spinner flask and a rotary wall vessel were performed. • Increasing impeller speed reduced the Kolmogorov length scales. • The Kolmogorov length scales were strongly correlated with cell aggregate sizes. • The rotary wall vessel was designed to minimize shear stress distributions. • The rotary vessel reduced shear stress distribution by half than the spinner flask.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 32 publications
6
22
0
Order By: Relevance
“…Compared to a standard 125ml spinner flask or bioreactor, each well in a 96-well plate requires a maximum of 350 μ l of media, which is approximately a 3.5-fold reduction in total media consumption. The elimination of mechanical stirrers and tubing resolves unwanted fluidic shear stress gradients, decreases damaging cellular collisions, and reduces labor-intensive culture maintenance [41, 42, 43]. Moreover, by seeding each spheroid in its own well, the samples may be kept biologically independent, providing enhanced statistics and throughput for assays.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to a standard 125ml spinner flask or bioreactor, each well in a 96-well plate requires a maximum of 350 μ l of media, which is approximately a 3.5-fold reduction in total media consumption. The elimination of mechanical stirrers and tubing resolves unwanted fluidic shear stress gradients, decreases damaging cellular collisions, and reduces labor-intensive culture maintenance [41, 42, 43]. Moreover, by seeding each spheroid in its own well, the samples may be kept biologically independent, providing enhanced statistics and throughput for assays.…”
Section: Resultsmentioning
confidence: 99%
“…Shear stress is a key factor in determining whether a bioreactor is suitable for the cultivation of shear-sensitive cells such as plant cells, mammalian cells, and stem cells (Ghasemian et al, 2020). Figure 10 shows the variation of shear stress with time in the cases of the initial and optimal Fig.…”
Section: Characteristics Of the Optimal Statementioning
confidence: 99%
“…In the unique environment of space, free fall-induced weightlessness can modulate the intrinsic factors of tissue mechanical environment leading to reduced mechanical loads in tissue niche environments [ 8 ]. Modeling the effects of microgravity on Earth has been attempted with a multitude of strategies; however, many of these strategies in an effort to replicate free fall, generate non-physiologic fluid shear and rotational loading to the cells [ 9 ]. The interesting observation that traditional static cell culture plating results in pressure loading well below the physiologically relevant range may provide a unique path for cellular level modeling of the microgravity free fall environment.…”
Section: Introductionmentioning
confidence: 99%
“…The most studied physical stress relevant to the EB model is fluid shear stress [ 14 ], imparted by spinner flasks [ 15 ] or microfluidic channels [ 16 , 17 ], or rotating wall vessels [ 9 ] used in their culture. Generally, these studies have shown that fluidic shear stress promotes growth and maturation; however, this general observation has been refined as the study of mechanical regulation of EBs has expanded.…”
Section: Introductionmentioning
confidence: 99%